PERAN LEMBAGA SWADAYA MASYARAKAT DALAM INOVASI SUMBER DAYA ALAM LOKAL DI MASYARAKAT (STUDI EKSPLORATIF) - Noviyanti, Kristina; Mardani, Ambara Saraswati; Simbolon, Gallex (Education For All, 2024)
This research is motivated by the problem of lack of public understanding in the use and management of natural resources into products through innovation. So it is hoped that the role of Non Governmental Organizations will be to help the community in terms of innovation regarding the use and management of local natural resources. The aim of this research is to determine the role of non-governmental organizations in local natural resource innovation in society. This research uses qualitative methods with an exploratory study approach. This research is located at the Non Governmental Organization, Alfa Omega Foundation which is located on Jalan Timor Raya KM.13, Mata Air Village, Kupang Tengah District, Kupang Regency, East Nusa Tenggara. The subjects in this research were the Director of the Alfa Omega Foundation, Deputy Director of the Alfa Omega Foundation, Head of the General Division, and the target community for the activities. The data collection techniques used were interviews, observation and documentation studies. Data analysis techniques include data collection, data reduction, data presentation. The triangulation used to explain the validity of the data is source triangulation and technical triangulation. The research results show that there are 4 (four) indicators of strategy, impact, value and benefits. Through the strategy carried out by the institution, it can have a positive impact on society. However, for the two indicators, namely the value and benefit indicators, there are new findings which will later be used as evaluation by the institution and the community.